Bloody, brutal, and barbaric? wrestling with troubling war texts - Webb, William J. 1957-; Oeste, Gordon K. (Westmont InterVarsity Press, 2019)
Christians cannot ignore the intersection of religion and violence. In our own Scriptures, war texts that appear to approve of genocidal killings and war rape raise hard questions about biblical ethics and the character of God. Have we missed something in our traditional readings? Identifying a spectrum of views on biblical war texts, Webb and Oeste pursue a middle path using a hermeneutic of incremental, redemptive-movement ethics.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books